A British national scandal: hunger, foodbanks, and the deployment of a Dickensian trope. Issue 1 (2nd January 2022) - Howarth, Anita
ABSTRACT: The normalization of foodbanks in Britain has sharply polarized public debates around issues of hunger. Government supporters laud their presence as a timely revival of an earlier tradition of voluntarism able to offset an unaffordable welfare state or stigmatize foodbanks as new spaces of 'dependency'. Government critics view foodbanks as a consequence of ministerial indifference to growing hunger and a betrayal of the core values envisaged by the founders of the welfare state. The very presence of foodbanks in one of the richest countries in the world is denounced as a national scandal that violates an intrinsic quality of Britishness and signifies a regression to an earlier, more heartless era. In mooting this argument, critics have deployed a Victorian trope that evokes familiar figures and narratives from popular culture in a circular social imaginary of 'what we were' in the Victorian era as distinct from 'what we have been' in the post-war welfare state to 'what we are reverting to' now. The paper critically deconstructs the trope as a device to hold the government to account while also critiquing its nostalgia rooted in a mythic notion of the welfare state which was never as inclusive as popular imagining would believe.